Comparison of ESP programming platforms - Filip Rak; Jozef Wiora (Institute of Advanced Engineering and Science, 2021)
The growing popularity of ESP boards has led to the development of several programming platforms. They allow users to develop applications for ESP modules in different programming languages, such as C++, C, Lua, MicroPython, or using AT commands. Each of them is very specific and has different advantages. The programming style, efficiency, speed of execution, level of advancement, or memory usage will differ from one language to another. Users mostly base their choice depending on their programming skills and goals of the planned projects. The aim of this work is to determine, which language is the best suitable for a particular user for a particular type of project. We have described and compared the mentioned languages. We have prepared test tasks to indicate quantified values. There is no common rule because each of the languages is intended for a different kind of user. While one of the languages is slower but simpler in usage for a beginner, the other one requires broad knowledge but offers availability to develop very complex applications.